(untitled) (International relations and international law Journal, 2026)
This article examines the conditions under which the Organization of Turkic States (OTS) can transition from symbolic-ideological coordination to sustainable economic integration. Its central focus is the structural «rhetoric–outcome» gap that emerges when political consolidation outpaces institutional implementability and material effects. The theoretical framework integrates regionalism, neofunctionalism, intergovernmental analysis, and geoeconomics. Empirically, the study follows an explanatory mixed-methods design combining comparative institutional analysis, process tracing, and a descriptive assessment of dynamics in trade, transit, investment, and regulatory compatibility. The findings show that pan-ideational solidarity is an important source of legitimacy and mobilization, but cannot ensure long-term sustainability unless converted into enforceable institutions. The resilience of the OTS depends on the quality of implementation mechanisms, the density of economic-policy coordination, and a balanced distribution of gains among participants. The Middle Corridor case highlights the dual nature of current trends: despite growing geoeconomic relevance, persistent infrastructural, regulatory, and governance constraints continue to limit reproducible integration effects. Scenario analysis identifies three trajectories of OTS evolution-inertial, limited-pragmatic, and transformational and demonstrates that only the transition to an «economic belt» model creates the preconditions for long-term organizational viability. The key policy implication is the need to move from declarative integration to managed economic cooperation based on enforceable commitments, project financing, measurable KPIs, and institutionalized performance monitoring. Key words: Organization of Turkic States (OTS), regional integration, pan-ideational solidarity, economic implementability, rhetoric-outcome gap, institutional coordination, Middle Corridor, geoeconomics, regulatory harmonization, transit connectivity, investment cooperation, scenario analysis.